Effects of conjugated linoleic acid supplementation after weight loss program on body weight status and metabolic parameters among overweight Iranians - Fouladi, Hanieh (2015)
Obesity is a crucial health related issue among human beings, and investigation to find a solution has been one of the most popular topics among researchers. Although there are some lifestyle changes and strategies to control obesity,using supplement or medication to help people lose weight is still under review. Conjugated linoleic acid (CLA) is one of the supplements that have been studied in the last decades to determine its impact on the weight loss, fat mass reduction, and energy expenditure, but the CLA’s mechanism of action is still unclear. The objective of this study is to determine the effect of CLA supplementation and combination of CLA and exercising on anthropometric measurements, lipid profiles, and inflammatory biomarkers. This study was a randomized controlled trial, and subjects were randomly assigned to participate in one of three groups named Control, CLA (the group receiving CLA supplementation without exercise), and CLA+E (the group that receive CLA supplementation in addition to exercising); two groups received 3 grams of CLA supplement which included a mixture of the bioactive isomers 50% cis-9, trans-11 and 50% trans-10, cis-12, but one of them was put on a moderate-intense training, and the control group neither received CLA supplement, nor was put on any training exercise. A total of 60 participants were recruited for each group (n=180), and the duration of study was 12 weeks. All the participants were on a moderate-balanced restricted calorie diet which was arranged to make them lose 4-6kg during 12 weeks of intervention, and the moderate intensity training was defined as walking with the speed of 5.5-6 km/h at least 160 minutes per week. 171 subjects completed their participation (Response Rate = 95%), and in comparison with the baseline body weight, Body Mass Index (BMI), Body Fat Mass (BFM), and waist to hip ratio of the CLA and CLA+E groups had a significant decrease (P < 0.05) with average BFM loss being 10.3% and 12% among CLA and CLA+E, respectively, compared to 2.7% among Control group. As for the biochemical analysis, the blood free fatty acid increased and high density lipoprotein decreased in CLA group which was an unfavorable effect of CLA supplementation. Although the supplementation alone appeared to have some non-desirable effects on the mentioned blood tests, this change did not occur among the exercise group. As a conclusion, supplementation with conjugated linoleic acid among overweight Iranians for 12 weeks reduced the BFM with some adverse effects on blood profiles which can be controlled through a moderate-intense exercise.